Proceso de atención de enfermería en paciente 65 años con accidente cerebro vascular. - Cajo Lemache, Mirian Narciza (2023)
The cerebrovascular accident is seen with a higher incidence in older adult patients, but it can also be seen in young adults since it is caused by the blockage of blood clots or arteriosclerotic plaques in the brain, which makes it impossible to supply blood to a certain part. of the brain tissue which will be affected by the lack of nutrients and oxygen. The objective of our work is to identify the nursing care that we are going to put into practice for the subsequent care of patients for speedy recovery. Since, as we know, this disease has dysarthria, neurological dysphagia, walking problems, difficulty seeing with one or both eyes as signs and symptoms. Since it is caused by bad eating habits, sedentary lifestyles, high blood pressure and other factors. The nursing care process is applied and a care plan and interventions based on the clinic and the human responses that are evidenced are carried out, to contribute to the therapeutic with care in the management of pharmacotherapies, emotional support and with surveillance and follow-up. Periodicals to evaluate the evolution of health actions, as expected results after the interventions carried out.